2013
DOI: 10.1007/s10661-013-3484-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring fish communities in wadeable lowland streams: comparing the efficiency of electrofishing methods at contrasting fish assemblages

Abstract: Electrofishing is considered a reliable tool to assess the assemblages and biodiversity of fish in wadeable streams. The most widely used electrofishing techniques (point [P], single-pass [S-P], and multiple-pass [M-P]) vary as to the effort needed for sample collection, and this may potentially influence the degree of accuracy. Moreover, little is known about the comparability of the methods and their specific performance in streams with different fish assemblages. The aim of this investigation was to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…We sampled fish from 150‐m stream reaches using single‐pass electrofishing (EFKO GmbH model FEG 1500). Single‐pass electrofishing has been shown to be adequate to detect trends in fish abundance and species richness given standardised effort (Bertrand, Gido & Guy, ; Sály et al ., ; Teixeira‐de Mello et al ., ), and is cost‐effective for large geographic‐scale studies (Meador, McIntyre & Pollock, ). We sampled standardised 150‐m long reaches because previous evaluations indicated that representative samples of fish species for small streams can be obtained from reaches 30–40 times the mean wetted width or at least 150 m (Reynolds et al ., ; Sály et al ., ; David et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…We sampled fish from 150‐m stream reaches using single‐pass electrofishing (EFKO GmbH model FEG 1500). Single‐pass electrofishing has been shown to be adequate to detect trends in fish abundance and species richness given standardised effort (Bertrand, Gido & Guy, ; Sály et al ., ; Teixeira‐de Mello et al ., ), and is cost‐effective for large geographic‐scale studies (Meador, McIntyre & Pollock, ). We sampled standardised 150‐m long reaches because previous evaluations indicated that representative samples of fish species for small streams can be obtained from reaches 30–40 times the mean wetted width or at least 150 m (Reynolds et al ., ; Sály et al ., ; David et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that the mean value of this indicator was higher than 1 for the barbel, suggesting that more individuals were using the fish lift compared to those that were available downstream and captured by electrofishing. As outlined above, such results should be analyzed with caution as most barbel, particularly the larger individuals, often dwell in deep pool habitats [9] where electrofishing is clearly less effective [74], and thus their population downstream that is potentially available to migrate could have been under-evaluated. The use of other techniques, such as mark-recapture or passive integrated transponders (PIT) telemetry [75], can be useful to provide more accurate data on barbel stocks arriving at the foot of large-scale barriers.…”
Section: Discussionmentioning
confidence: 99%
“…MANAGEMENT BRIEF produced data of comparable precision for evaluation of CPUE trends (similar to Teixeira-de Mello et al 2014) for the more common species. The potential increase in the variety of habitats sampled during continuous electrofishing suggests that this method may better address the collection of "whole assemblage" monitoring data, similar to the conclusions of Vehanen et al (2013).…”
Section: Covariatementioning
confidence: 99%
“…The potential increase in the variety of habitats sampled during continuous electrofishing suggests that this method may better address the collection of "whole assemblage" monitoring data, similar to the conclusions of Vehanen et al (2013). Additionally, the collection of rare taxa may be critical to monitoring programs and continuous electrofishing yielded greater species richness (similar to Teixeira-de Mello et al 2014), including seven relatively rare species that were only collected in continuous samples (versus two species collected only in point samples). The results suggest that continuous electrofishing would be particularly appropriate for collecting presence-absence data as rare species typically lead to difficulties in producing meaningful abundance analyses (Angermeier and Smogor 1995;MacKenzie et al 2005;Maxwell and Jennings 2005).…”
Section: Covariatementioning
confidence: 99%
See 1 more Smart Citation